These are the reasons for student users of online transportation services in the city of Semarang turning to Maxim - Aurra Amalia Dwiputri; Ahmad Munif; Zurika Estiyarika; Khairani Zikrinawati; Zulfa Fahmy (LPPM Institut Studi Islam Sunan Doe, 2024)
This study aims to analyze the effect of service and price perceptions on satisfaction among students using Maxim in Semarang City. The subjects used were 161 people with the criteria of having or using the Maxim application, and students or equivalent in Semarang City. For processing the data using the help of IBM SPSS version 26. The results of the study showed its significance of 0.00 <0.05, which means that there is a significant influence between service perceptions, price perceptions on customer/student satisfaction. Perceptions of service obtained a t value of 17.885 > 1.960 t table with a significance value of 0.00 <0.05, this means that there is an influence between service perceptions and satisfaction. Then for price perceptions obtained by t count results of 9.624 > 1.960 t table with a significance value of 0.00 <0.05 this means that there is an influence between price perceptions and satisfaction. Then for the F value calculate 168.159 and sig. count as 0.00. So that the calculated F value is 168.159 > 3.05 F table and the significance value is 0.00 < 0.05.This means that there is a significant influence on service perception (X1) and price perception (X2) on satisfaction (Y).